2006
DOI: 10.1128/mcb.01392-06
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of New Human Origins of DNA Replication by an Origin-Trapping Assay

Abstract: Metazoan genomes contain thousands of replication origins, but only a limited number have been characterized so far. We developed a two-step origin-trapping assay in which human chromatin fragments associated with origin recognition complex (ORC) in vivo were first enriched by chromatin immunoprecipitation. In a second step, these fragments were screened for transient replication competence in a plasmid-based assay utilizing the Epstein-Barr virus latent origin oriP. oriP contains two elements, an origin (dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 76 publications
4
41
0
Order By: Relevance
“…5E). As shown previously with endogenous ORC2 (19), the FLAG-ORC2 wild type protein bound to both origins of replication in G 1 /S phase cells but did not do so in G 2 …”
Section: Phosphorylation Of Orc2 Dissociates Orc From Origin Ofsupporting
confidence: 80%
See 2 more Smart Citations
“…5E). As shown previously with endogenous ORC2 (19), the FLAG-ORC2 wild type protein bound to both origins of replication in G 1 /S phase cells but did not do so in G 2 …”
Section: Phosphorylation Of Orc2 Dissociates Orc From Origin Ofsupporting
confidence: 80%
“…Origin trapping experiments have shown that the human ORC dissociates from the replication origins during the S phase and later in the cell cycle (19). The ORC2-GFP, which is diffusely distributed in nuclear area during early mitosis, binds rapidly to anaphase chromatin in Drosophila embryos (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the simplest and most promising approach of isolating nascent DNA strands is: (i) to lyse cells directly in the wells of alkaline agarose gels; (ii) to separate DNA by electrophoresis under denaturing conditions and (iii) to isolate short single-stranded DNA by gel extraction 12 . This procedure minimizes sample handling and has been previously employed by others to map oris in mammalian cells 13,14 . This simple method also appears to minimize DNA damage because origin enrichment was not found with nonreplicating control DNA 10 .…”
Section: Experimental Designmentioning
confidence: 99%
“…Following pre-RC assembly in G1 phase, ORC disassembles partially as ORC1 is degraded while ORC2-6 remains stable and keeps an association with chromatin (Méndez et al, 2002;Tatsumi et al, 2003). The association of human ORC with chromatin and replication origins is regulated during the cell cycle, showing increased association in G1/S compared to G2/M phases (Gerhardt et al, 2006;Prasanth et al, 2004;Siddiqui and Stillman, 2007). ORC3 shows no obvious colocalisation with replication foci suggesting a displacement from replicating chromatin; however, in late S phase cells a weak and apparently euchromatic population of ORC3 remains detectable (see figure 6 of Siddiqui and Stillman, 2007).…”
Section: Concordant Dynamics For Y Rnas and Orcmentioning
confidence: 99%